2016
DOI: 10.1002/chem.201600079
|View full text |Cite
|
Sign up to set email alerts
|

Platinum–Copper Nanoframes: One‐Pot Synthesis and Enhanced Electrocatalytic Activity

Abstract: Platinum-copper nanoframes were produced from copper nanoparticles by a one-pot synthesis method. The growth mechanism was thoroughly studied by experiment and theoretical calculations. Owing to the unique structure, Pt-Cu nanoframes exhibited significantly enhanced catalytic activity toward the electro-oxidation of methanol compared to commercial Pt black.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Oxidative etching is one of the most popular etching strategies, especially the synthesis of PtCu-based NFs occupies an absolute predominance 65 . The statistics above further validate the vital role of oxidative etching in the formation of NFs, particularly for the PtCu-based NFs is benefited from the oxidative etching due to the simple operation and excellent structure 35,66 . A series of progressive reports on PtCu-based NFs such as octopod cubic PtCu, concave cubic PtCu, rhombic dodecahedral PtCuNi and rhombic dodecahedral PtCuRh NFs, emphasized the critical role of oxidative etching in the one-step synthesis of PtCu-based NFs 38,40,41 .…”
Section: Oxidative Etchingsupporting
confidence: 54%
“…Oxidative etching is one of the most popular etching strategies, especially the synthesis of PtCu-based NFs occupies an absolute predominance 65 . The statistics above further validate the vital role of oxidative etching in the formation of NFs, particularly for the PtCu-based NFs is benefited from the oxidative etching due to the simple operation and excellent structure 35,66 . A series of progressive reports on PtCu-based NFs such as octopod cubic PtCu, concave cubic PtCu, rhombic dodecahedral PtCuNi and rhombic dodecahedral PtCuRh NFs, emphasized the critical role of oxidative etching in the one-step synthesis of PtCu-based NFs 38,40,41 .…”
Section: Oxidative Etchingsupporting
confidence: 54%
“…To maximize the utilization of Pt for a variety of reactions, much effort has been focused on constructing favored nanostructures, including hollow or open nanostructures. More recent studies suggested that bimetallic PtNi and PtCu nanocrystals with hollow and open structures have attracted great interest as electrocatalysts due to their large surface area-to-volume ratio and three-dimensional accessible surface. However, with concern for the acidic environment, most of the synthesized frame-like nanocrystals in recent reports are Pt-enriched entirely, and thus the utilization of Pt is still important due to the uselessness of Pt atoms in inner atomic layers of the edges.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the aforementioned analysis, Figure exhibits the formation mechanism of PtCu DNFs. As reported previously, the presence of CTAC would weaken the interactions between Pt­(acac) 2 and OAm . On the basis of this assumption, Cu 2+ ions are preferentially reduced to metallic Cu atoms by allantoin and OAm served as the coreductants, followed by the quick coverage of the adjacent CTAC and allantoin molecules.…”
Section: Results and Discussionmentioning
confidence: 99%